Familial paroxysmal kinesigenic dyskinesia is associated with mutations in the KCNA1 gene. (27th December 2017) - Yin, Xiao-Meng; Lin, Jing-Han; Cao, Li; Zhang, Tong-Mei; Zeng, Sheng; Zhang, Kai-Lin; Tian, Wo-Tu; Hu, Zheng-Mao; Li, Nan; Wang, Jun-Ling; Guo, Ji-Feng; Wang, Ruo-Xi; et al.
Abstract: Paroxysmal kinesigenic dyskinesia (PKD) is a heterogeneous movement disorder characterized by recurrent dyskinesia attacks triggered by sudden movement. PRRT2 has been identified as the first causative gene of PKD. However, it is only responsible for approximately half of affected individuals, indicating that other loci are most likely involved in the etiology of this disorder. To explore the underlying causative gene of PRRT2 -negative PKD, we used a combination strategy including linkage analysis, whole-exome sequencing and copy number variations analysis to detect the genetic variants within a family with PKD. We identified a linkage locus on chromosome 12 (12p13.32–12p12.3) and detected a novel heterozygous mutation c.956 T>G (p.319 L>R) in the potassium voltage-gated channel subfamily A member 1, KCNA1 . Whole-exome sequencing in another 58 Chinese patients with PKD who lacked mutations in PRRT2 revealed another novel mutation in the KCNA1 gene [c.765 C>A (p.255 N>K)] within another family. Biochemical analysis revealed that the L319R mutant accelerated protein degradation via the proteasome pathway and disrupted membrane expression of the Kv1.1 channel. Electrophysiological examinations in transfected HEK293 cells showed that both the L319R and N255K mutants resulted in reduced potassium currents and respective altered gating properties, with a dominant negative effect on the Kv1.1 wild-type channel. Our study suggests that these mutations in KCNA1 cause the Kv1.1 channel dysfunction, which leads to familial PKD. The current study further extended the genotypic spectrum of this disorder, indicating that Kv1.1 channel dysfunction maybe one of the underlying defects in PKD.